Single-cell resolution of plasma cell fate programming in health and disease - Delaloy, Celine; Schuh, Wolfgang; Jäck, Hans-Martin; Bonaud, Amelie; Espeli, Marion (European Journal of Immunology, 2021)
Long considered a homogeneous population dedicated to antibody secretion, plasma cell phenotypic and functional heterogeneity is increasingly recognized. Plasma cells were first segregated based on their maturation level, but the complexity of this subset might well be underestimated by this simple dichotomy. Indeed, in the last decade new functions have been attributed to plasma cells including but not limited to cytokine secretion. However, a proper characterization of plasma cell heterogeneity has remained elusive partly due to technical issues and cellular features that are specific to this cell type. Cell intrinsic and cell extrinsic signals could be at the origin of this heterogeneity. Recent advances in technologies such as single cell RNA-seq, ATAC-seq, or ChIP-seq on low cell numbers helped to elucidate the fate decision in other cell lineages and similar approaches could be implemented to evaluate the heterogeneous fate of activated B cells in health and disease. Here, we summarized published work shedding some lights on the stimuli and genetic program shaping B-cell terminal differentiation at the single cell level in mice and men. We also discuss the fate and heterogeneity of plasma cells during immune responses, vaccination, and in the frame of human plasma cell disorders.
CRIS-Team WoS Importer:2021-12-24